POTENSI SISTEM PERTANIAN ORGANIK DALAM KONSERVASI MUSUH ALAMI HAMA DAN SERANGGA NETRAL PADA TANAMAN SAYURAN DI LAHAN GAMBUT (Potency Of Organic Agricultural System In Conservation Of Natural Energy And Different Environment In Vegetable Plants In Grave La: Melhanah1 , Supriati, L.1 , dan Saraswati, D1 - Administrator Journal (AgriPeat, 2018)
ABSTRACKThe purpose of this research is to know the potential of organic farming in the conservation ofnatural enemies of important pests and neutral insects on the ecosystem of sweet corn and longbean vegetables in peatlands Kalampangan Urban Village Palangka Raya. The study wasconducted on an area of 210 m2, divided into 12 plots planted sweet corn and long beans withorganic and conventional treatment. Observations were made at 2-8 MST. Samples were takenusing sweep nets (for canopy arthropods), pitfall traps (for ground surface arthropods) and lighttraps (for nocturnal arthropods). The results showed: organic vegetables potentially developed inthe effort of conservation of natural enemies and neutral insects with indicators as follows: 1). Thenumber of insects found in organic and conventional plots consists of predators (84.11%),parasitoids (8.49%) and neutral insects (7.40%); 2). The predator species richness in organic longbean plants is higher than conventional (R = 2.711 and 1.811). The predominant predominance ofsweet corn and long bean organic plants is Gryllidae (C = 0.331), Formicidae (C = 0.465) andMiridae (C = 0.109); 3). The richness of parasitoids and neutral insects in organic sweet corn ishigher than conventional (R = 1,265 and 1,193). Types of parasitoids and neutral insectsdominating organic and conventional vegetables are Braconidae and Scarabaeidae with values0.444 and 0.423.Keywords: organic vegetables, natural enemies, neutral insects, pests, peat